2020
DOI: 10.3390/su12145509
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Handicap Sections and Situations to Improve Driving Safety of Automated Vehicles

Abstract: An automated vehicle performs self-driving by utilizing information gathered through sensors attached to the vehicle. Sensor accuracy is thus mentioned as the major technology for enhancing driving safety. However, since urban centers are replete with sections and situations that handicap driving such as sensor recognition limitations and failures, it is necessary to conduct a study that prepares for driving handicaps. As such, this study aims to derive the sections and situations where driving safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…They concluded that adverse weather conditions, such as rainfall and snowfall, affect accidents [ 20 , 21 , 22 , 23 ]. Additionally, based on the studies, another study that derives and analyzes factors affecting self-driving cars’ driving safety also confirmed that bad weather conditions need to be studied first to ensure driving safety [ 24 ].…”
Section: Introductionmentioning
confidence: 91%
“…They concluded that adverse weather conditions, such as rainfall and snowfall, affect accidents [ 20 , 21 , 22 , 23 ]. Additionally, based on the studies, another study that derives and analyzes factors affecting self-driving cars’ driving safety also confirmed that bad weather conditions need to be studied first to ensure driving safety [ 24 ].…”
Section: Introductionmentioning
confidence: 91%
“…The data for the mixed road driving cycle is ambiguous due to behaviors, obstacle segments caused by environmental factors [41], Therefore, we discard the data of the mixed road driving cycle in this s the three-type classification experiments on the cleaned data, w expressway driving cycle, the suburban road driving cycle, and the u…”
Section: Dataset and Comparison On The Three-classes Of Cleaned Datamentioning
confidence: 99%
“…The data for the mixed road driving cycle is ambiguous due to irregular driving behaviors, obstacle segments caused by environmental factors [41], or driving faults. Therefore, we discard the data of the mixed road driving cycle in this section.…”
Section: Dataset and Comparison On The Three-classes Of Cleaned Datamentioning
confidence: 99%
“…In subsequent research, a substantial number of studies have been based on PilotNet's end-to-end architecture. A combination of visual temporal dependencies of the input data have been considered in [15] and a convolutional long short-term memory (C-LSTM) network has been proposed for steering control. In [16], surround-view cameras were used for end-to-end learning.…”
Section: Related Workmentioning
confidence: 99%